Pengaruh Kualitas Layanan, Relational Bonding, Dan Brand Image Terhadap Loyalitas Nasabah - Endang Prihatiningsih; Soffia Pudji Estiasih (BIP's JURNAL BISNIS PERSPEKTIF, 2019)
In today's banking industry experienced sharp competition, which requires BRI banks to improve their performance, among others, by improving the services quality is one key to business success. Besides the BRI banks must maintain a brand image that is good in the eyes of their customers, and continue to establish harmonious long-term relationships with its customers so that customers remain loyal to the BRI Bank Branch of Jombang. This study aims to test and analyze relationships partially or simultaneously service quality, relational bonding and brand image of customer loyalty BRI Bank Branch of Jombang. While the population in this study all customers of BRI Bank Branch of Jombang and the sample of this study was 90 with sampling techniques that were accidental sampling that is customers who easily found and willing to fill out the questionnaire that the author proposed. The analysis technique uses multiple linear regression analysis with SPSS Version 20.0. The results of partial hypothesis test is 1) service quality not significant effect on customer loyalty with sig. = 0.817 > 0.05 so the hypothesis is rejected; 2) relational bonding significant effect on customer loyalty with sig. = 0.003 < 0.05, so the hypothesis is accepted; 3) brand image significant effect on customer loyalty with sig. = 0.001 < 0.05 so the hypothesis is accepted. The results of simultaneously is service quality, relational bonding and brand image have a significant effect on customer loyalty with Sig. = 0.000 < 0.05 so the hypothesis is accepted.